Collection of information for the determination of machine reliability indicators - Tatevosov, V. (Запоріжжя : 2024, 2024)
EN: The initial information about the reliability of the machines should provide determination of its level and evaluation with numerical indicators. Information about the reliability of machines and their elements can be obtained on the basis of tests using special methods, as a result of observing the operation of machines in operation and analyzing their technical condition during maintenance and repair. The most valuable and accessible for manufacturers are operational observations and analysis of the technical condition of machine elements during maintenance and repair. The information collection system is a set of organizational and technical measures to obtain the necessary and reliable information about reliability. Information collection documents include primary forms of operational information accounting and accumulative forms. The first ones are intended for recording unsystematised information: one-time documents on failure – failure card and repair card to eliminate the consequences of failure; record of work and failures. Tractors with a run time of no more than 200 engine hours and agricultural machines with a run time of no more than 10% of the average seasonal norm are taken under observation if all refusals from the start of operation are known. Machines, one of the units of which had a failure of complexity group II from the beginning of operation, are not examined.
Keywords: maintenance; repair; operational bservations; analysis of the technical condition